BETWEEN ILLNESS AND DEATH: A COMPLICATED SITUATION TO LIVE - Giraldo Toro, Jenny (Investigación y Educación en Enfermería, 2009)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Objective: to reflect about the present days practice of nursing and to sensitize from a personal experience the professional nurse responsibility towards the terminally ill patient. The patient was 51 years old. Fourteen years before she was diagnosed with left breast mammal cancer. Ten years after she developed ovary methastasis and two years later right breast methastasis. Two years after this diagnostics she had lung methastasis. Her family was upset since illness is a very difficult situation to bear. The mother´s sufferings, pain and weeping made her daughter a vigorous person facing a difficult struggle that helps to discover the nursing profession a as a life option. Conclusion: usually society does not recognize, exalts and remembers the nursing professionals. But the opportunity to be night and day in a hospital accompanying the ill mother made her understand that nursing in her life would to be self expression more than a life option